A systematic review of the prevalence and odds of domestic abuse victimization among people with dementia. (2nd September 2016) - McCausland, Beth; Knight, Lucy; Page, Lisa; Trevillion, Kylee
Abstract: Little is known about the prevalence of domestic abuse in later life or after the onset of dementia. Given the expanding population of dementia sufferers, it is imperative to identify the degree to which domestic abuse occurs within this population. The aim of this study was to establish the prevalence (lifetime and past year), odds, and trajectory of domestic abuse victimization among people with dementia. Systematic searches of 20 electronic databases were performed from inception to June 2016, using a pre-defined search strategy for English language articles containing data on the prevalence and/or odds of adult lifetime or past year domestic abuse among people with dementia. Six studies met the inclusion criteria. Among patients with dementia, the past year median prevalence of physical and psychological domestic abuse victimization is 11% and 19%, respectively. Findings from cross-sectional studies show an increased odds of domestic abuse among people with dementia vs those without. Trajectory information indicated that domestic abuse was more prevalent in relationships with a pre-morbid history of abuse. The lack of research into this area is highlighted by the small number of includable studies. There is a need for further research into the impact of dementia on domestic abuse.